The Mediating Effect of Risk Perception on the Relationship Between Social Presence and Impulsive Buying in Live Streaming Shopping - Purboyo; Zulfikar, Rizka; Wahyuni, Amalia; Herawaty, Ana Sofia; Rina, Rina (INTERNATIONAL JOURNAL OF ECONOMICS, MANAGEMENT, BUSINESS, AND SOCIAL SCIENCE (IJEMBIS), 2024)
This study aimed to examine the impact of social presence on impulsive buying mediated by risk perception in live streaming shopping using social presence theory. The phenomenon of live streaming shopping had become a major trend in e-commerce in Indonesia, with a large audience through various marketplace applications. Celebrity endorsers played an important role in grabbing the attention of the audience, so direct interaction with them could trigger impulsive buying behavior. This study was exploratory research, proposing four problem formulations related to the social presence of celebrity endorsers, viewers, and products, as well as risk perceptions that affected impulsive purchases. The purpose of the study involved testing the influence of the social presence of celebrity endorsers, viewers, and products on consumer risk perception, as well as the role of risk perception mediation on impulsive purchases. This study used a survey method with a population consisting of people in the South Kalimantan province who were viewers of live streaming shopping. Data collection was carried out by distributing questionnaires online to 186 respondents. Data analysis involved testing the validity and reliability of the instrument, and using SEM-PLS. The results of this study found that (1) the social presence of celebrity endorsers, viewers, and products had a significant effect on risk perception, (2) the social presence of viewers and products had a significant effect on impulsive purchases, while the social presence of celebrity endorsers had no influence on impulsive purchases, and (3) risk perception had a mediating role in the relationship between the social presence of celebrity endorsers, viewers, and products with impulsive purchase behavior.